Comparison of emulsifying properties of fibrils formed from whey protein concentrate following induction by nuclei and nuclei fragments. (December 2021) - Wang, Xin; Yue, Chonghui; Xu, Honghua; Guan, Chen; Guo, Ruichi; Yang, Xiaotong; Ma, Caihong; Shao, Meili
Abstract: The structural and emulsification properties of amyloid fibrils in whey protein concentrate (WPC) with certain ratios of added nuclei or nuclei fragments, generated using ultrasound, high-speed shear treatment and enzymatic hydrolysis methods, were compared. The emulsifying properties of nuclei fragments produced by high-speed shear treatment were effectively improved, but those of nuclei hydrolysed by alkaline protease decreased, since the determinant structures were destroyed. However, the emulsifying activity index and emulsifying stability index of fibrils subsequently formed by nuclei fragment induction (enzymatic hydrolysis method) were higher than those of fibrils formed by the heat-induced method and nuclei induction method in all pH environments. The fibril size induced by nuclei fragment induction was smaller, and the fibril level was higher, and thus the ability to improve the emulsifying properties of WPC was stronger.